2001
DOI: 10.1074/jbc.m008763200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Endogenous Retrovirus-K10 Protease in Cell-free and Cell-based Assays

Abstract: A full-length and C-terminally truncated version of human endogenous retrovirus (HERV)-K10 protease were expressed in Escherichia coli and purified to homogeneity. Both versions of the protease efficiently processed HERV-K10 Gag polyprotein substrate. HERV-K10 Gag was also cleaved by human immunodeficiency virus, type 1 (HIV-1) protease, although at different sites. To identify compounds that could inhibit protein processing dependent on the HERV-K10 protease, a series of cyclic ureas that had previously been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…A previous report showed that HIV-1 protease is capable of cleaving HERV-K Gag in vitro (33). Therefore, if HERV-K Gag coassembles with HIV-1 virion components, HIV-1 protease is likely to cleave the HERV-K Gag in the same virion.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report showed that HIV-1 protease is capable of cleaving HERV-K Gag in vitro (33). Therefore, if HERV-K Gag coassembles with HIV-1 virion components, HIV-1 protease is likely to cleave the HERV-K Gag in the same virion.…”
Section: Resultsmentioning
confidence: 99%
“…While no single human endogenous retrovirus sequence thus far identified in the genome encodes a complete infectious virus, the diverse HK2 loci in the human genome retain coding capacity for every functional retroviral protein (4,10,(28)(29)(30): the Gag protein, necessary for particle formation and release (31)(32)(33)(34)(35); the Pro protein, necessary for cleavage and maturation of viral proteins (35)(36)(37); the Pol protein, necessary for RNA-dependent DNA replication and integration (38)(39)(40)(41)(42); the accessory protein Rec, which exports unspliced viral RNA from the nucleus to the cytoplasm (43,44); and functional Env proteins (45). Recombination or trans-complementation between these proviruses could lead to the formation of viruses that would be able to package and transmit HK2 sequences (9,(46)(47)(48), as seen with endogenous retroviruses in mice (49)(50)(51).…”
mentioning
confidence: 99%
“…Additionally, the specific ARV used would need to have activity against the retrovirus targeted and the retrovirus would need to be actively producing infectious viral particles. If targeting HERV type K would be beneficial in PALS, which is still unknown, then a reasonable regimen might consist of two NRTIs and one INSTI given the data above (38)(39)(40)(41). The cost of the specific ARV regimen would depend on the drug(s) selected.…”
Section: Dosing and Costsmentioning
confidence: 99%
“…The current evidence, taken from in vitro studies, suggests that HERV type K is susceptible to most members of a class of ARVs called nucleoside reverse transcriptase inhibitors (NRTIs; 38,39), but is relatively resistant to ARVs from the class protease inhibitors (PIs; [38][39][40][41]. Evidence for in vitro efficacy of non-nucleoside reverse transcriptase inhibitors (NNRTIs) and integrase inhibitors (INSTIs) is mixed (38,39).…”
Section: Mechanismsmentioning
confidence: 99%